Evaluating gullying effects on modeling erosive responses at basin scale. (January 2019) - Millares, A.; Díez-Minguito, M.; Moñino, A.
Abstract: The objective of this research was to assess the effect of gullying on the erosive response at the basin scale by modeling. For this purpose, a distributed hydrological model, which includes erosion by raindrop, rilling and gullying, was configured and applied in a Mediterranean basin in southern Spain. The results show a range of parameters close to those provided by the literature and good agreement with field measurements. However, the simulations indicate that the rill erodibility parameter at the surface is overestimated by as much as 70% to compensate for gullying processes. Other parameters, such as the subsoil erodibility of the soil profile, play an important role in the erosive response of the basin. A geomorphological threshold for sediment yield that relates density of gullies and erodibility parameters was found. These responses are especially relevant in semiarid environments where the intense pulses of precipitation have important effects on landscape evolution. Highlights: Soil erodibility is overestimated to compensate gullying processes. A geomorphological threshold relates gully density and erodibility. Subsoil erodibility has a prominent role in erosive response. Measuring gullying remains an important challenge at the basin scale.